DESIGN OF A FUZZY CONTROLLER FOR SOLAR PV ARRAY FED WATER PUMPING SYSTEMS - SAFAALDEEN, RUAA R.; HASSAN, LOKMAN H. (Journal of Duhok University, 2021)
The purpose of this paper is a designing an efficient solar Photovoltaic Water Pumping System (PVWPS) by using a three phase induction motor. Two adaptive fuzzy logic controllers are proposed to control the dc-link voltage and the induction motor speed. A combination between of fuzzy logic and gain-scheduling controller is proposed to design the adaptive Fuzzy Gain-scheduling Proportional and Integral (FGPI) controllers. A linearized model is considered for the system using small signal model. The performances of the PVWPS using the proposed controllers are set side by side to those gotten from the classic Proportional plus Integral (PI) controllers. The simulation results demonstrated that the suggested controllers are effective in enhancing the dynamic performance of the system